1997
DOI: 10.1023/a:1018444325085
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fluorescence in situ hybridization (FISH) with probes representing sheep satellite I and satellite II DNAs shows a different distribution of the two repetitive DNA families in the centromeric region of most chromosomes. The single signal per chromosome produced by the satellite I probe suggests close proximity of this DNA family to the primary constriction. Satellite II produces two separate signals on the sister chromatids, and large blocks of satellite II DNA constitute most of the short arm of all acrocentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…BovB-LINE1 constituted a major fraction of the LINE retrotransposons, consistent with the expansion of these elements during the evolution of the Bovidae (Szemraj et al 1995; Adelson et al 2009; Nilsson et al 2012). We also found that approximately 536 Mb of the genome was composed of an 804 bp bovine-specific satellite DNA, which is usually located in the centromeric and pericentric regions of chromosomes (D’Aiuto et al 1997; Kopecna et al 2014).…”
Section: Resultsmentioning
confidence: 83%
“…BovB-LINE1 constituted a major fraction of the LINE retrotransposons, consistent with the expansion of these elements during the evolution of the Bovidae (Szemraj et al 1995; Adelson et al 2009; Nilsson et al 2012). We also found that approximately 536 Mb of the genome was composed of an 804 bp bovine-specific satellite DNA, which is usually located in the centromeric and pericentric regions of chromosomes (D’Aiuto et al 1997; Kopecna et al 2014).…”
Section: Resultsmentioning
confidence: 83%
“…DNA satellite I is located mainly at or near centromeres ( D'Aiuto et al ., 1997 ). As expected, sequences were detected on every acrocentric autosome.…”
Section: Discussionmentioning
confidence: 99%
“…A significant portion of eukaryotic genomes is represented by repeated sequences, among which a large fraction includes sequences repeated in tandem, known as satellite DNAs (for a review, see Plohl et al ., 2008 ), often located at or near the centromeres ( D'Aiuto et al ., 1997 ). A typical satellite DNA is composed of thousands of monomeric units, arrayed in tandem in head-to-tail configuration and located in constitutive heterochromatin ( Plohl et al ., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cenDNA probe, on the other hand, hybridized to the region between satI and satII domains. The distribution of satellite DNA into separate domains has www.nature.com/scientificreports/ been previously described among others, in sheep, Kirk's dik-dik and dama gazelle [39][40][41] and more broadly within the Bovinae 26 .…”
Section: Resultsmentioning
confidence: 74%